PENGUATAN MATERI FISIKA DASAR MENGGUNAKAN ALAT PERAGA KIT SEDERHANA BERBASIS MIKROKONTROLER ARDUINO UNO DI MAN 1 SELONG, KABUPATEN LOMBOK TIMUR - Suhayat Minardi; Rahadi Wirawan; Dian Wijaya Kurniawidi; Susi Rahayu; Arif Budianto; Laili Mardiana; Intan Utami; Dodi Mariadi (Jurnal Abdi Insani, 2023)
Community service is part of the Tri Dharma of Higher Education which must be implemented. As an aspect of their mandatory duties, all campus academics have an obligation to carry out community service. Community service can be carried out using various methods, models, strategies and service topics. One of these topics is strengthening or deepening basic physics material using teaching aids and based on the application of technology that is widely used. This activity was carried out with the aim of providing reinforcement of basic physics material for students at MAN 1 Selong, East Lombok Regency. This service is also aimed at introducing the use of microcontrollers as learning tools. The service is divided into three sub-stages, namely an introduction to material on quantities in physics, providing examples of cases of analysis of physical quantities, and simple training on operational methods for microcontrollers as data processing elements and temperature sensors. This stage is carried out using the Arduino IDE application. This activity provides benefits for students in increasing direct understanding regarding the temperature quantity which is a basic quantity, the unit conversion process, and the application of digital technology in measurement activities. Students are trained to apply Arduino IDE devices, Arduino UNO microcontrollers, and create basic programming with Arduino IDE. Students can also more easily measure temperature and other quantities using tools designed independently and display the results on the screen. Students are able to carry out temperature unit conversions manually and also through programming. The application of a microcontroller can make it easier for students to carry out data analysis. The results of this service can improve students' understanding of basic physics material. Students are able to use microcontrollers and design teaching aids.